Test-Retest Reliability of an Isometric and Isometric/Vibratory Muscular Strength Protocol with Functional Electro-Mechanical Dynamometry - Oscar Andrades-Ramírez; David Ulloa-Díaz; Bryan Alfaro Castillo; Patricio Arroyo-Jofré; Antonio Castillo-Paredes; Luis Chirosa-Ríos (MDPI AG, 2024)
The purpose of the study was to analyze the test-retest reliability of an isometric and isometric/vibratory muscular strength protocol in the bilateral seated bench press (BSBP), bilateral seated rowing (BSR), unilateral seated right knee extension (USKER), and left knee extension (USKEL) tests controlled using functional electromechanical dynamometry (FEMD) in healthy young adults. A repeated measures design was used to determine the reliability of a muscular strength protocol in isometric and isometric vibration modes with FEMD. No significant differences were found in test-retest analysis (p > 0.05; ES < 0.20); and high reliability (CV = 4.65-5.02%; ICC = 0.99-0.98) was found for BSBP measures, and acceptable reliability (CV = 3.71-9.61%; ICC = 0.98-0.95) was found for BSR, USKER, and USKEL. Furthermore, the coefficients between the two measures were strong (r = 0.963-0.839) and highly significant (p = 0.001) for maximal strength in the isometric and maximal isometric/vibratory assessment of muscle strength in all muscle strength tests. This study demonstrates that isometric and maximal isometric/vibratory strength in the BSBP, BSR, USKER, and USKEL tests can be measured with high reliability and reproducibility using the FEMD.